Shelf Life Estimation of “So Lite” Fish Nugget - Amalia, Ulfah (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2012)
Fish nugget is a food product with a high degree of risk because it has a degree of acidity greater than 4.5 and more than 0.85 for water activity. Based on this risk, the companies generally put storage adviceinformation on the fish nuggets packaging, as a quality parameter of the product. One method that is  simple enough to be applied in the expected shelf life by measuring the rate of decline in the quality parameter is Arrhenius model. The purpose of this analysis was to determined the basis used by a  company  in the food product shelf-life estimation in this case is a nugget of fish products with trademarks  Fish Nugget '’So Lite". Based on the plot between the effect of storage temperature on storage time, obtained by equation y = -6.18 ln (x) + 309.2 in the regression (R2 = 0.999). Regression values indicates that the allegations made by the companies of fish nugget is true because R2>0.75. Assumptions used by the companies might be associated with activity of microorganism, where an increased along with increase in temperature. Keywords: fish nugget, shelf life, quality, Arrhenius